The Spirit and Politics - Loewenstein , Bedřich (Dějiny – teorie – kritika, 2013)
This study examines conceptual influences which after the WWII shaped the intellectual profile of the well known German political scientist Kurt Sontheimer (1928-2005). His political philosophy was inspired by the journalistic work of Thomas Mann. Mann’s inner development from an apologist towards a decided critic of German irrationalism and anti-democratism helped Sontheimer arrive at his mature political and conceptual views. A reconstruction of the attitude of German churches towards the republic and Nazi barbarism is included in order to help outline a less known aspect of Sontheimer as a Protestant critic of the German Federal Republic.